Immune checkpoint inhibitor-associated myopathy: a clinicoseropathologically distinct myopathy. Issue 2 (2nd November 2020) - Shelly, Shahar; Triplett, James D; Pinto, Marcus V; Milone, Margherita; Diehn, Felix E; Zekeridou, Anastasia; Liewluck, Teerin
Abstract: Immune checkpoint inhibitors have revolutionized the landscape of cancer treatment. Alongside their many advantages, they elicit immune-related adverse events, including myopathy, which potentially result in substantial morbidity if not recognized and treated promptly. Current knowledge of immune checkpoint inhibitor-associated myopathy is limited. We conducted a 5-year retrospective study of patients with immune checkpoint inhibitor-associated myopathy. Clinical features, survival and ancillary test findings were analysed and compared with those of immune-mediated necrotizing myopathy patients without immune checkpoint inhibitor exposure seen during the same time period. We identified 24 patients with immune checkpoint inhibitor-associated myopathy (median age 69 years; range 28–86) and 38 patients with immune-mediated necrotizing myopathy. Ocular involvement occurred in 9/24 patients with immune checkpoint inhibitor exposure, without electrodiagnostic evidence of neuromuscular transmission defect, and in none of the immune-mediated necrotizing myopathy patients ( P < 0.001). Myocarditis occurred in eight immune checkpoint inhibitor-associated myopathy patients and in none of the immune-mediated necrotizing myopathy patients ( P < 0.001). Median creatine kinase was 686 IU/l in the immune checkpoint inhibitor cohort (seven with normal creatine kinase) compared to 6456 IU/l in immune-mediated necrotizing myopathy cohort ( P < 0.001). Lymphopenia was observed in 18 and 7 patients with and without immune checkpoint inhibitor exposure, respectively ( P < 0.001). Myopathological findings were similar between patients with and without immune checkpoint inhibitor exposure, consisting of necrotic fibres with no or subtle inflammation. Necrotic fibres however arranged in clusters in 10/11 immune checkpoint inhibitor-associated myopathy patients but in none of the immune checkpoint inhibitor-naïve patients ( P < 0.001). Despite the lower creatine kinase levels in immune checkpoint inhibitor-exposed patients, the number of necrotic fibres was similar in both groups. Immune checkpoint inhibitor-associated myopathy patients had a higher frequency of mitochondrial abnormalities and less number of regenerating fibres than immune-mediated necrotizing myopathy patients ( P < 0.001). Anti-hydroxy-3-methylglutaryl-CoA reductase or signal recognition particle antibodies were absent in patients with immune checkpoint inhibitor exposure but positive in two-thirds of immune checkpoint inhibitor-naïve patients. Most patients with immune checkpoint inhibitor-associated myopathy responded favourably to immunomodulatory treatments, but four died from myopathy-related complications and one from myocarditis. Intubated patients had significantly shorter survival compared to non-intubated patients (median survival of 22 days; P = 0.004). In summary, immune checkpoint inhibitor-associated myopathy is a distinct, treatable immune-mediated myopathy with common ocular involvement, frequent lymphopenia and necrotizing histopathology, which contrary to immune-mediated necrotizing myopathy, is featured by clusters of necrotic fibres and not accompanied by anti-hydroxy-3-methylglutaryl-CoA reductase or signal recognition particle antibodies. Normal or mildly elevated creatine kinase level does not exclude the diagnosis. Abstract : This is a comprehensive analysis of a large cohort of patients with immune checkpoint inhibitor-associated myopathy. Shelly et al. highlight its unique features of ocular involvement and normal creatine kinase levels in some patients, mimicking myasthenia gravis. Multifocal clusters of necrotic fibres are characteristics and occur in even patients without hyperCKemia. Graphical Abstract: